LOW-COST AUTOMATIC TIMER SYSTEM ADAPTED TO COOKING APPLIANCES (FULafia Journal of Science and Technology, 2026)
This study presents the development and implementation of a low-cost automatic timer system specifically adapted for cooking appliances. Recognising the growing need for user-friendly and efficient cooking solutions, the system aims to enhance culinary experiences by automating timing functions for various cooking processes. Leveraging microcontroller technology and sensor inputs, the system offers precise timing control, ensuring optimal cooking results while minimising user intervention. It employs the ESP32 microcontroller, which is programmed to trigger a relay actuator ON or OFF according to the input received from the timer circuit. It is equipped with a 16x2 LCD to monitor the timing sequence in conjunction with an IoT app that can be used to also control and monitor the timer system. The automatic timer system offers versatility and ease of use for a wide range of cooking scenarios and appliances. This research contributes to the field of smart kitchen technology, emphasising the importance of affor-dability and accessibility in the development of automated solutions for everyday cooking tasks. Future work will focus on expanding the system’s capabilities, including integration with smart home technologies and additional cooking functionalities.
Keywords: Microcontroller; ESP32; Relay; IoT; Timer system; LCD